Tidal and Ocean Current Energy - Rafael Morales; Eva Segura (Journal of Marine Science and Engineering, 2023)
Renewable energy resources (for example, wind, solar or ocean currents, among others) possess an enormous potential, owing to the fact that they are a pollution-free and inexhaustible resource [...]